Analisis Produktivitas Perikanan Budidaya Kolam Tanah Pembenihan Ikan Nila (Oreochromis niloticus) (Studi Kasus: Pembudidaya di Kecamatan Wanayasa, Kabupaten Purwakarta) - Dewi, Annisa Permata; Suryana, Asep Agus Handaka; Nurhayati, Atikah; Maulina, Ine (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research was carried out in Wanayasa District, Purwakarta Regency with research time from December 2023 – June 2024. The aim of this research is to describe the cultivation profile regarding its suitability to the CPIB and the level of aquaculture productivity as well as analyzing factors that can influence the productivity of land pond aquaculture. tilapia fish hatchery. Sampling in this research was carried out using a purposive sampling method, meanwhile the data obtained was analyzed using qualitative and quantitative descriptive methods. The results of the research show that the cultivation profile in the technical aspect of cultivation is in accordance with the provisions stated in SNI 8035:2019 concerning Good Fish Hatchery Methods. Based on the results of the analysis of the productivity level of tilapia fish hatchery cultivation in Wanayasa District, Purwakarta Regency, it can be seen from the productivity per unit area with a productivity value of 2139 fish/cycle/m² and seen from the productivity per unit cost with a productivity value of 10 in units of IDR/head. The financial analysis carried out resulted in a profitable R/C ratio value of 1.2. The factors that influence fisheries productivity are fish broodstock and total pond area, while age, length of cultivation experience, and labor do not have a significant influence.